2022
DOI: 10.1017/s0950268822001546
|View full text |Cite
|
Sign up to set email alerts
|

Household transmission of the Delta COVID-19 variant in Queensland, Australia: a case series

Abstract: Household transmission plays a key role in the spread of Covid-19 through populations.In this paper, we report on the transmission of Covid-19 within households in a metropolitan area in Australia, examine the impact of various factors and highlight priority areas for future public health responses. We collected and reviewed retrospective case report data and follow-up interview responses from households with a positive case of the Delta Covid-19 variant in Queensland in 2021. The overall secondary attack rate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This assumption is supported by the finding that those who encouraged their families and friends to get vaccinated are more likely to accept a COVID-19 vaccination [82]. The presence of symptoms may also be relevant for a secondary transmission from index cases, as symptomatic infections have been described to increase transmissibility from the index cases [83]. Finally, the behavior may be different between households of vaccinated and unvaccinated index cases.…”
Section: Discussionmentioning
confidence: 95%
“…This assumption is supported by the finding that those who encouraged their families and friends to get vaccinated are more likely to accept a COVID-19 vaccination [82]. The presence of symptoms may also be relevant for a secondary transmission from index cases, as symptomatic infections have been described to increase transmissibility from the index cases [83]. Finally, the behavior may be different between households of vaccinated and unvaccinated index cases.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies reported a poor adherence to self-isolation rules and the need for a better information about isolation/quarantine protocols from public health officials [7]. Home health care workers care for played an important role in supporting patients with confirmed and suspected COVID-19 who remain at home [8,9].…”
Section: Introductionmentioning
confidence: 99%